Microstructure, mechanical properties and formability of friction stir processed interstitial-free steel - Sekban, D. M.; Saray, Onur; Aktarer, S. M.; Purcek, G.; Ma, Z. Y. (Elsevier Science Sa, 2015)
The microstructure, mechanical properties and stretch formability of fine-grained (FG) interstitial-free steel (IF-steel) formed by friction stir processing (FSP) was investigated systematically. One-pass FSP drastically refined the microstructure with aid of dynamic recrystallization (DRX) mechanism during processing and formed volumetric defect free basin-like processed region (PR) with a mean grain size of 5 mu m (initial grain size was 40 mu m). This microstructural evolution brought about a considerable increase in both hardness and strength values of IF-steel without considerable decrease in ductility values. Also, strain hardening dominated deformation behavior was obtained with the FSPed samples as an essential property for the engineering application. Coarse-grained (CG) IF-steel demonstrated high formability with an Erichsen index (El) of 2.88 mm. Grain refinement by FSP yielded very close El value of 2.80 mm with increasing punch load (F-El). Force-displacement curves obtained in each process conditions reflected a similar membrane straining regimes where samples uniformly thinned under biaxial tension loads with aid of strain hardening capability. The formation of FG microstructure by FSP reduced the roughness (orange peel effect) of the free surface of biaxial stretched sample by decreasing the nonuniform grain flow leading to the so-called orange peel effect. It is concluded that a good balance of strength, ductility and strain hardenability along with equivalence formability to CG condition can be achieved by FSP as a single step practical procedure. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: IF-steels; Friction stir processing; Grain refinement; Formability